Design, synthesis, and bioevaluation of imidazo [1, 2–a] pyrazine derivatives as tubulin polymerization inhibitors with potent anticancer activities. (15th December 2022) - Deng, Bulian; Sun, Zhiqiang; Wang, Yuxi; Mai, Ruiyao; Yang, Zichao; Ren, Yichang; Liu, Jin; Huang, Junli; Ma, Zeli; Chen, Ting; Zeng, Canjun; Chen, Jianjun
Graphical abstract: Highlights: Novel imidazo[1, 2–a]pyrazine derivatives were discovered as potential tubulin inhibitors. TB-25 exhibited the strongest inhibitory effects against HCT-116 cells with an IC50 of 23 nM. TB-25 effectively inhibited tubulin polymerization in vitro and destroyed the dynamic equilibrium of microtubules in HCT-116 cells. TB-25 dose-dependently induced G2/M phase cell cycle arrest and apoptosis in HCT-116 cells. TB-25 suppressed HCT-116 cell migration in a concentration-dependent manner. Abstract: Through structural optimization and ring fusion strategy, we designed a series of novel imidazo[1, 2–a]pyrazine derivatives as potential tubulin inhibitors. These compounds displayed potent anti-proliferative activities (micromolar to nanomolar) against a panel of cancer cell lines (including HepG-2, HCT-116, A549 and MDA-MB-231 cells). Among them, compound TB-25 exhibited the strongest inhibitory effects against HCT-116 cells with an IC50 of 23 nM. Mechanism studies revealed that TB-25 could effectively inhibit tubulin polymerization in vitro, and destroy the dynamic equilibrium of microtubules in HCT-116 cells. In addition, TB-25 dose-dependently induced G2/M phase cell cycle arrest and apoptosis in HCT-116 cells. Furthermore, TB-25 suppressed HCT-116 cell migration in a concentration-dependent manner. Finally, molecular docking showed that TB-25 fitted well in the colchicine binding site of tubulin and overlapped nicely with CA-4. Collectively, these results suggest that TB-25 represents a promising tubulin inhibitor deserving further investigation.